RESISTANCE OF Phaseolus vulgaris L. WILD AND PROGENIES WITH CULTIVATED BEANS TO THE COMMON WEEVIL Acanthoscelides obtectus (SAY) AT FIELD AND LABORATORY LEVEL - POSSO-GÓMEZ, CARMEN ELISA; FLOWER-VALOR, JOSÉ; SCHOONHOVEN, AART VAN (Revista Colombiana de Entomología, 1985)
Under field and laboratory conditions 26 genotypes of the common bean Phaseolus vulgaris L. were evaluated for resistance to the bean weevil Acanthoscelides obtectus (Say). Artificial infestations of adults of A. obtectus were made in the field when the bean plants were mature. Ten pods/ genotype were harvested and brought to the laboratory for evaluation of resistance. At the same time, pods and seeds without A. obtectus damage were harvested and evaluated for resistance under laboratory conditions. Statistical differences for resistance parameters were found among genotypes in both field and laboratory infestations. The wild bean lines G12952, G12891, and G10019 showed high levels of resistance to A. obtectus in comparison to the susceptible checks V8030, V7920, and Diacol Calima. F4 genotypes showed similar levels of resistance or susceptibility as they did in the previously evaluated F3 generation. In the field infestation, significant differences were found among genotypes for the number of oviposition perforations in the pods and for the number of larval penetrations in the seed. Significant correlations were found between the number of adults that emerged from laboratory infested seeds and the number of adults emerged from -field infested pods, and among the three parameters (number of adults, life cycle, and dry weight of adults) evaluated for pods and seed in the laboratory. These results suggest that both infested pods and seeds can be used for evaluating A. obtectus resistance in bean genotypes.